Evaluation of factors associated with vertical HIV‐1 transmission - Matheus Costa da Rosa; Rubens Caurio Lobato; Carla Vitola Gonçalves; Naylê Maria Oliveira da Silva; Maria Fernanda Martínez Barral; Ana Maria Barral de Martinez; Vanusa Pousada da Hora (Brazilian Society of Pediatrics, 2015)
Objective: To compare the prevalence and factors associated with vertical transmission of human immunodeficiency virus 1 (HIV-1) among pregnant women treated in the periods of 1998‐2004 and 2005‐2011 in a reference service for the care of HIV‐infected patients in southern Brazil. Methods: This was a descriptive and analytical study that used the databases of laboratories from the CD4 and STDs/AIDS Viral Load National Laboratory Network of the Brazilian Ministry of Health. HIV‐1‐infected pregnant women were selected after an active search for clinical information and obstetric and neonatal data from their medical records between the years of 1998 to 2011. Results: 102 pregnant women were analyzed between 1998 and 2004 and 251 in the period between 2005 and 2011, totaling 353 children born to pregnant women with HIV‐1. It was observed that the vertical transmission rate was 11.8% between 1998 and 2004 and 3.2% between 2005 snf 2011 (p < 0.001). The increased use of antiretroviral drugs (p = 0.02), the decrease in viral load (p < 0.001), and time of membrane rupture lower than 4 h (p < 0.001) were associated with the decrease of vertical transmission factors when comparing the two periods. Conclusion: It was observed a decrease in the rate of vertical transmission in recent years. According to the studied variables, is suggested that the risk factors for vertical transmission of HIV‐1 were absence of antiretroviral therapy, high viral load in the pregnant women, and membrane rupture time > 4 h.